THE MEANING OF SITOU TIMOU TUMOU TOU AS A MODEL OF WOMEN EMPOWERMENT MANAGEMENT IN MAPALUS HOUSE IN SOUTHEAST MINAHASA, NORTH SULAWESI - Treesje Imran; Laurens Mambu; Beatrix Lapalelo; Yongker Baali; Patricia Jeaneth Cyntia Kojongian (JURNAL MANAJEMEN MAKER STIE SULTAN AGUNG, 2023)
Si Tou Timou Tumou Tou is a philosophy of the Minahasa people, meaning that humans live to humanize others. The term "tou" in Si Tou refers to humans as individuals who must first 'live' to be able to enliven others ('tumou tou'). Meanwhile, Mapalus house represents a local wisdom model in the form of collaborative efforts to build houses for the Tounsawang ethnic community in Southeast Minahasa, passed down through generations. Mapalus house consists of 10 to 30 people, and anyone can become a member, regardless of gender. The division of labor, based on the principle of togetherness in mutual construction and enlivening, known as Sitou Timou Tumou Tou, is carried out reciprocally for each house to be built, where the roles of women and men are equal in work responsibilities. The main research question is how Sitou Timou Tumou Tou holds meaning for women in the Mapalus House work, empowering themselves individually and others. The research was conducted in the Tombatu district, Southeast Minahasa Regency, known for its strong Mapalus house tradition, with three villages as research samples: Tombatu 1, Tombatu II, and Betelen. The qualitative method employed focused on observation, interviews, key informants, and analysis of observation and interviews. The research results indicate that the meaning of Si tou timou tumou tou is deeply rooted in women, allowing them to persist in Mapalus house. The understanding of Sitou Timou Tumou Tou empowers women individually, socially, and economically within Mapalus house. This empowerment is attributed to principles such as mutual enlivening, starting with the term 'tou,' signifying individual empowerment before extending to others. Mapalus house provides space and access for women to develop themselves individually in both domestic and public functions. A communal organizational culture is built within Mapalus house, fostering mutual assistance between women and men without subordination and patriarchy. Despite modernization and technological advancements, the meaning of 'tou' in Si Tou Timou Tumou Tou as local wisdom remains strong, upheld as tradition and respected by the entire Tounsawang ethnic community. Consequently, the meaning of Sitou Timou Tumou Tou is powerful within women individually, enabling them in both family (domestic) and community (public) contexts.